2021
DOI: 10.3389/fdgth.2021.683090
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Human Papillomavirus Vaccine Promotions and Hesitancy in Northern California Through Examining Public Facebook Pages and Groups

Abstract: Human papillomavirus (HPV) vaccination coverage among adolescents is lower in rural regions and remains under the 80% coverage goal by Healthy People 2030. Through both sentiment analysis and topic modeling, this research examines how local health agencies and groups in nine Northern California counties promote HPV vaccines through Facebook and how target populations react to promotion posts in comments that elucidate their sentiments and hesitancy toward HPV vaccination. In January 2021, we identified 2,105 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 37 publications
(53 reference statements)
3
5
0
Order By: Relevance
“…More specifically, although most students and residents reported being aware of HPV vaccination, a large shift in responses indicated that more respondents felt they had insufficient knowledge and information about the HPV vaccine specifically, which corresponded with a decrease in personal importance of HPV vaccination. This information corresponds with and supports the findings of other recent research that describes an overall increase in the number of people (and providers) who feel they have inadequate knowledge and insufficient information about the HPV vaccine to make clear, rational decisions for their children based upon evidence [37][38][39].…”
Section: Discussionsupporting
confidence: 89%
“…More specifically, although most students and residents reported being aware of HPV vaccination, a large shift in responses indicated that more respondents felt they had insufficient knowledge and information about the HPV vaccine specifically, which corresponded with a decrease in personal importance of HPV vaccination. This information corresponds with and supports the findings of other recent research that describes an overall increase in the number of people (and providers) who feel they have inadequate knowledge and insufficient information about the HPV vaccine to make clear, rational decisions for their children based upon evidence [37][38][39].…”
Section: Discussionsupporting
confidence: 89%
“…According to Facebook, 1 “pages are places on Facebook where artists, public figures, businesses, brands, organizations and non-profits can connect with their fans or customers.” In contrast, “groups are a place to communicate about shared interests with certain people.” Facebook pages are often seen as broadcasting channels that send messages out to their followers while Facebook groups are deemed as communities that emphasize common interests and interactions among group members. 2 One study that examines public pages vs. groups related to vaccines concludes that “public pages may work more efficiently to have targeted vaccine campaigns for organizations or institutions than setting up public group discussions.” ( Zhang et al, 2021 , p. 10) When using the CrowdTangle API to search through its database, we included all post types in English Language, regardless whether the post was branded content or not. We only included verified accounts because we are interested in content by legitimate users.…”
Section: Methodsmentioning
confidence: 99%
“…For example, LIWC calculates positive emotions in a given document by counting the percentage of words that appear in the dictionary indicating positive emotions. It has been widely used to analyze health-related conversations on social media and identify the public’s emotions and attitudes [ 26 ].…”
Section: Methodsmentioning
confidence: 99%